Comparative analysis of the diagnostyc value of CT and MRI in the assessment of peritoneal carcinomatosis in ovarian cancer - Yu. A. Soloveva; N. A. Rubtsova; E. G. Novikova; D. O. Kabanov; S. A. Skugarev (Исследования и практика в медицине)
Purpose of the study. To study the diagnostic effectiveness of computed tomography (CT) and multiparametric magnetic resonance imaging (mmMRI) in preoperative assessment of the prevalence of peritoneal tumor lesions with the calculation of the peritoneal carcinomatosis index in patients with advanced ovarian cancer (AOC), in comparison with the results of surgical revision and postoperative histological examination.Patients and methods. The study included 75 patients with acute respiratory viral infections who underwent examination and treatment at the Kaluga Regional Clinical Oncology Dispensary in the period from 2019 to 2023. All patients underwent CT, mmMRI and diagnostic laparoscopy (DL) as part of the preoperative assessment of peritoneal carcinomatosis, the results of which were compared with the data of the postoperative histological examination. In 75 (100 %) patients, mmMRI was performed using a standard protocol; in 39 (52 %) cases, the standard mmMRI protocol was modified and supplemented with the collection of diffusion weighted imaging (DWI) data in the coronary plane, with a common coverage area of all floors of the abdominal cavity, including the pelvis. Depending on the mpMRI protocol used, the patients were divided into two groups: 1st group consisted of 36 (48 %) patients with acute respiratory viral infections (standard protocol), 2nd group included 39 (52 %) patients (modified protocol).Results. The use of mmMRI at the preoperative stage made it possible to obtain a higher diagnostic efficiency in assessment of the operitoneal carcinomatosis prevalence, compared with CT data, especially with locuses of 5 mm or less localized at the level of the right dome of the diaphragm, along the peritoneum in the small intestine and its mesentery. The inclusion in the MRI protocol of DWIs with a high b-factor in the coronary projection, with a field of view covering all floors of the abdominal cavity, made it possible to achieve information content comparable to the data of the DL. When assessing the probability of detecting foci of peritoneal carcinomatosis during mmMRI in patients with ovarian cancer (OC) in group 2, in comparison with the DL data, the area under the ROC curve was 0.940 ± 0.010 with 95 % CI: 0.921–0.959 (p < 0.001). The sensitivity and specificity of mpMRI were 96.4 % and 93.5 %, respectively, PPV – 97.9 %, NPV – 89.1 %.Conclusion. The importance of diagnostic information on the prevalence of peritoneal carcinomatosis at the stage of planning treatment tactics in patients with AOC requires improvement of examination algorithms and unification of methodological approaches during CT and MRI. In order to increase diagnostic effectiveness, it is necessary to introduce into clinical practice mmMRI with the inclusion of high-b-factor DWI in the protocol, performed in two projections.: axial and coronary. The field of view, which simultaneously covers all floors of the abdominal cavity, improves the information content of the diagnosis of peritoneal and lymph node lesions during the preoperative examination of patients with AOC. This approach makes it possible to perform a full-fledged mapping of the abdominal cavity with the calculation of the peritoneal carcinomatosis index (PCI), potentially avoiding "mute zones" resulting from technical gaps that can be observed when performing MRI in two separate blocks, according to the nomenclature of studies on anatomical areas (MRI of the abdominal cavity and pelvis).